Pengaruh Lingkungan Kerja, Upah Serta Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt. Sariguna Primatirta Tbk. Cikarang Jawa Barat - Sofyan Wahyono; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract             This study aims to determine the effect of simultan and partial work environment, wages and motivation on employee performance at PT. Sariguna Primatirta Tbk. The sample of this study were all employees, amounting to 75 respondents. Sampling using saturated sampling that is using all members of the population into the sample. The data collection method in this study used a questionnaire and documentation. Data analysis method used in this study is multiple linear regression.            The results of this study indicate that the work environment, wages and motivation simultaneously have a significant effect on employee performance, the work environment has a positive and significant effect on employee performance, wages have a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance. Keywords : Work Environment, Wages and Motivation